Manajemen Literatur Kelabu sebagai Pendukung Penelitian dan Penulisan Karya Ilmiah - Ernawati, Endang (Bina Nusantara University, 2006)
Article explores the role of grey literature in supporting research and the writing of scientific articles in Indonesia. The discussion covers introduction of grey literature terminology, forms, causes, sources, level of confidentiality, users’ view, and ts development. It is concluded that the grey literature have not been well managed by its institutions; The Indonesia government has paid much attention to the collection, management, and documentation of grey literature; Internet development help the dissemination of grey litearature information in which users can easily access through the website; And the publication of local e-Content in some universities are still in the process of development due to the copy right and facilities problems.